2013
DOI: 10.1155/2013/723158
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Chitosan Conjugated Nanoparticles for Improving Tumor-Targeted Drug Delivery

Abstract: Objective. To prepare folic acid-chitosan conjugated nanoparticles (FA-CS NPs) and evaluate their targeting specificity on tumor cells. Methods. Chitosan (CS) NPs were prepared by ionic cross linking method, and folic acid (FA) was conjugated with CS NPs by electrostatic interaction. The properties of NPs were investigated, and doxorubicin hydrochloride (Dox) as a model drug was encapsulated for investigating drug release pattern in vitro. The cytotoxicity and cellular uptake of FA-CS NPs were also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…[28][29][30][31] It has been demonstrated that the FA conveniently binds to the surface of metals via noncovalent interactions 31,32 and similar method of interaction with CS were also reported. 33 In this particular instance, the conjugation of the FA and CS is initiated due to the strong electrostatic interaction of the cationic amino groups of CS with the anionic carboxylate group of FA; the result shows a loading efficiency of approximately 30.5±1.2 wt.%. 33 Despite the successes recorded following noncovalent method of conjugation of FA to other biomolecules or MNPs, [29][30][31][32][33][34] several work reported a superior performance following covalent methods of interactions.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…[28][29][30][31] It has been demonstrated that the FA conveniently binds to the surface of metals via noncovalent interactions 31,32 and similar method of interaction with CS were also reported. 33 In this particular instance, the conjugation of the FA and CS is initiated due to the strong electrostatic interaction of the cationic amino groups of CS with the anionic carboxylate group of FA; the result shows a loading efficiency of approximately 30.5±1.2 wt.%. 33 Despite the successes recorded following noncovalent method of conjugation of FA to other biomolecules or MNPs, [29][30][31][32][33][34] several work reported a superior performance following covalent methods of interactions.…”
mentioning
confidence: 91%
“…33 In this particular instance, the conjugation of the FA and CS is initiated due to the strong electrostatic interaction of the cationic amino groups of CS with the anionic carboxylate group of FA; the result shows a loading efficiency of approximately 30.5±1.2 wt.%. 33 Despite the successes recorded following noncovalent method of conjugation of FA to other biomolecules or MNPs, [29][30][31][32][33][34] several work reported a superior performance following covalent methods of interactions. 4,35,36 However, the greatest challenge is meeting the requirements of specific conjugation chemistry that retains QDs biochemical activity as much as possible.…”
mentioning
confidence: 91%
“…Moreover, several targeting molecules such as FA have also been conjugated with chitosan NPs in order to facilitating their selective function (Table 4). It is reported that FAconjugated DOX-loaded chitosan NPs could potently kill FR-expressing SMMC-7221 cells, in vitro [144]. FA-tagged copper ion and acetylacetone-encapsulated chitosan NPs were also exerted anti-tumor effects on the several FRoverexpressing cancer cells, in vitro [145].…”
Section: Chitosan Nanoparticlesmentioning
confidence: 98%
“…Folate-targeted chitosan NPs intracellular delivery was more target specific than non targeted ones (Senthilkumar et al 2015). In another Karmali et al (2009) study, folate-conjugated chitosan NPs showed greater cytotoxicity and uptake in folate receptor expressing cells (Song et al 2013). Transferrin receptors (TfRs) are expressed in all nucleated cells in the body, such as red blood cells, erythroid cells, hepatocytes, intestinal cells, monocytes (macrophages), and the BBB (Zhong et al 2001).…”
Section: Targeted Drug Deliverymentioning
confidence: 99%